A quantitative assessment of economic impact of trade wars and the "Make in India" program - Badri Narayanan; Rahul Sen; Chidambaran Iyer; Sangeeta Khorana; Sadhana Srivastava (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
In a unique attempt, our paper aims to provide a quantitative economic assessment of the impact of "Make in India", a flagship program for industrialization, launched by the Government of India in 2014, combining it with the global trade war of 2017-18. We analyze whether the expected favourable impact of the former was reversed due to its reactive policies compared its pro-active policies, and whether it worsened due to the trade war, whose effects continue to aggravate in a post-COVID recalibration of global supply chains. The question assumes significance as Make in India program's proactive measures to boost investment may have a favourable impact on the industries at large in terms of output and employment. In contrast, its protectionist measures involving tariff barriers may have an ambiguous effect on the same. We utilize an applied general equilibrium analysis, exploring the impact of Make in India and the global trade war in a combined way. Our results suggest that the combined effects of both policies, while being beneficial for the Indian economy, yields negative ramifications for exports, jobs, and investment growth. Specific sectors are also unable to increase domestic output despite being a part of Make in India, such as the Chemical, Rubber, and Plastics industries, and those that use it as raw materials.
Keywords: F15; F61; O53; 330; Make in India; GTAP model; Trade war; COVID-19 pandemic; employment